Analysis of The Meaning of “Mehamat Man Kalimbubu, Metenget Ersenina, Metami Man Anak Beru” in the Tradition of Rakut Sitelu in the Karo Community - Rambe, Oktaviani Rahmatin; Manalu, Arafat; Sembiring, Kartika Patricia S; Lubis, Ilman Nafi’an; Muliana, Dina; Wuriyani, Elly Prihasti (CV. Rayyan Dwi Bharata, 2025)
Indonesia is a country that has a diversity of ethnic groups totaling 1,340. One of them is the Karo tribe who live around Deli Serdang Regency, Binjai City, Medan City, Stabat, Dairi Regency and Karo Regency. The Karo tribe has a kinship system concept called